Ignorance, hasard, incertitude, risque : des enjeux pour une éducation scientifique émancipatrice - Maryline Coquidé (Nantes Université, 2018)
The school is primarily concerned with learning and knowledge. The knowledge, especially scientific knowledge, is presented as liberating, which corresponds to a figure of emancipation, described by Galichet (2014) as "classic" and based on reason. I present here a complementary figure, which is based on the will and autonomy, "modern" according Galichet. I develop emancipatory potential of demonstration of ignorance and treatment of chance, uncertainty and of risk, in a scientific education. These approaches often neglected develop critical thinking and autonomy which are factors of emancipation.